Michael Howard y Ted Wheelwright (comps.). The Struggle for Development. Essays in Honour of Ernst Utrecht. Burnaby, B.C.: Simon Fraser University, International Studies Programme, 1990. 131 pp. - Devalle, Susana B. C. (El Colegio de México, 1993)
-